The effect of failed transfer of passive immunity and agammaglobulinemia on the occurrence of preweaning diarrhea, pneumonia, and mortality in Holstein calves - Mely T. Olivera; Jesús Mellado; José E. García; Juan A. Encina; Perpetuo Álvarez; Ulises Macías-Cruz; Leonel Avendaño; Miguel Mellado (Spanish Journal of Agricultural Research)
Aim of study: To evaluate the effect of failed transfer of passive immunity (FPI; Brix% < 8, equivalent to serum immunoglobulin G <10.1 g/L) and agammaglobulinemia (AG; Brix% ≤ 6.5, equal to 0 g/L serum immunoglobulin G) assessed with a digital Brix refractometer on the occurrence of pre-weaning diarrhea, pneumonia and mortality in Holstein female calves.